Professional Selection and its Relationship to Motivation Towards Learning among Tenth Graders in West Khan Yunis Governorate – Palestine - Dahlan, Mohammed Monther Yousef (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the level of appropriate professional selection and its relationship to motivation towards learning among tenth graders in West Khan Yunis Governorate, Gaza Strip. The study tools represented in the scales of professional choice, motivation towards learning prepared by the researcher, were applied to the study sample consisting of (240) tenth grade students for the school year (2020,2021), The researcher followed the descriptive approach and program to analyze the study data. The results concluded the following.: There is a high level of appropriate professional selection, motivation towards learning, and there is a statistically significant relationship between professional choice and motivation towards learning. Additionally, there are no statistically significant differences among the study sample in the level of appropriate professional selection, attributable to gender and selection a major. Also, there are statistically significant differences among the study sample in the level of motivation towards learning, attributable to gender. Also there are statistically significant differences among the subjects in the level of motivation towards learning attributable to gender, in favor of females, there are statistically significant differences among the study sample in the level of motivation towards learning due to the variable of selection amajor in favor of the scientific stream and the literary, based on the results, the researcher recommended activating the role of educational and family institutions, educational and psychological counselors in carrying out the counseling process for professional and academic selection, and directing the media (visual and audio) to play their role in spreading awareness of the necessity of professional choice and its importance in choosing academic disciplines, and attention to extra- curricular activities in guidance and counseling. Vocational, such as field visits to available professions to help discover students’ professional tendencies and develop their abilities, and to include in the curricula the topic of vocational choice and its importance in the academic stages in proportion to the characteristics of each age stage, and to conduct further studies in the field of vocational and academic choice for tenth grade students.
Keywords: professional selection; motivation towards learning; among tenth graders